Media and technology in 21st century higher and tertiary education in Africa : insights from teachers' colleges in Zimbabwe - Tandi, Costain; Mawere, Munyaradzi; Mukwazhe, Martin (Langaa RPCIG, 2023)
This book interrogates media and technology in the 21st century higher and tertiary education in Africa. Using Zimbabwe as its case study, the book highlights the immense changes that the digital revolution has brought to higher institutions of learning in Africa, including changes in teaching and learning. Framed from an anti-colonial perspective, the book argues that digital change, though critical in revolutionising education in Africa, has come with a price as it has resulted in some epistemological erasures and injustices meted against the poor. The book makes a critical contribution as it quests to correct the misdemeanours and injustices caused by digital gaps in African societies. The authors argue that the future and success of digital technology in Africa lie in how well African countries will culturally and contextually sensor technology and attend to the problems caused by digital gaps. The book provides a re-invigorated overview and nuanced analyses of the role of media and technology in revolutionising 21st century higher and tertiary education in Africa. It provides pointers and insights on how African countries can reformulate their education policy in a manner that is in sync with the level of digital technology of the time. This is an important addition to critical debates on media and technology studies in education in Africa.
Who should guard the police? Media and educators
Keywords: Education, Higher -- Effect of technological innovations on -- Africa.; Educational technology -- Africa.; Enseignement supérieur -- Effets des innovations sur -- Afrique.; Technologie éducative -- Afrique.; Society & social sciences.; SOCIAL SCIENCE / Ethnic Studies / American / African American & Black Studies.; Education, Higher -- Effect of technological innovations on; Educational technology; Africa